Work on conservation of animal genetic resources by the International Livestock Centre for Africa (ILCA) - Trail, J.C.M. (Food and Agriculture Organization of the United Nations, 1981)
Discusses ILCA's contribution towards the conservation of animal genetic resources, particularly studies on trypanotolerant livestock in West & Central Africa and evaluation of the potential of the Sahiwal breed to contribute to milk & beef production programs in Africa.